2016
DOI: 10.1002/slct.201600849
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Turkey β1-Adrenergic Receptor by Membrane Rafts - Insight from Molecular Dynamics

Abstract: G-protein coupled receptors are targets for ~70% of drugs. These receptors are responsible for signal transduction within a cell membrane (and further into the cell) and disruption to this signaling cascade is responsible for several non-infectious diseases. Membrane rafts exhibit significantly altered properties in comparison to fluid bilayers and as such may regulate certain GPCR's, or be responsible for errors in signaling. Using molecular dynamics, we have investigated the conformations of the turkey β1-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Additionally, long-time scale AA simulations have shown the influence of cholesterol on the conformational dynamics of several GPCRs, including β 1 AR, β 2 AR, 5-HT 1 A R, and 5-HT 2 A R. , As an example, microsecond simulations unveiled reduced conformational variability of β 2 AR caused by cholesterol binding (Figure C), suggesting an allosteric modulation of β 2 AR . Long-time scale simulations have also characterized a special modulatory effect of cholesterol on stabilizing the secondary structure of an amphipathic juxtamembrane helix in CB 1 , a class A GPCR, and mGluR2, a class C GPCR.…”
Section: Special Lipidsmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, long-time scale AA simulations have shown the influence of cholesterol on the conformational dynamics of several GPCRs, including β 1 AR, β 2 AR, 5-HT 1 A R, and 5-HT 2 A R. , As an example, microsecond simulations unveiled reduced conformational variability of β 2 AR caused by cholesterol binding (Figure C), suggesting an allosteric modulation of β 2 AR . Long-time scale simulations have also characterized a special modulatory effect of cholesterol on stabilizing the secondary structure of an amphipathic juxtamembrane helix in CB 1 , a class A GPCR, and mGluR2, a class C GPCR.…”
Section: Special Lipidsmentioning
confidence: 94%
“…393 Cholesterol is also known to alter the dynamics of GPCRs. 411 Its binding has been shown to alter the conformational dynamics of β 1 AR 412 and β 2 AR. 413 A μs-AA simulation showed that cholesterol binding at the helical interface limits the conformational variability of β 2 AR, 413 thus establishing an allosteric role for cholesterol in modulation of the protein.…”
Section: Membrane Receptorsmentioning
confidence: 99%